Integrated GIS Based Approach in Mapping Groundwater Potential Zones in Kota Kinabalu, Sabah, Malaysia - Isnain, Zulherry; Akhir, Juhari Mat (Geological Agency, 2017)
DOI:Â 10.17014/ijog.4.2.111-120The shortage of clean water occurs almost everywhere around the world. The demand for water supply increases from time to time due to various problems such as development, population growth, pollution, global warming, agricultural activities, logging, and so on. This study was conducted in the vicinity of Kota Kinabalu, Sabah, by using the Geographic Information System (GIS) for mapping the groundwater potential zones. The main objective of this study was to generate the predictive map of groundwater potential zones in the studied area through the integration of various thematic maps by using the GIS. This study includes five stages, namely collection and preparation of basic data, data analyses, development of space database, spatial analyses, and space integration. There are eleven parameters used in this study, namely rainfall, drainage, soil type, landuse, lithology, lineament density, topography, slope steepness, the ratio of sand and clay, major fault zones, and syncline zones. By using the Heuristic method, the final map of groundwater potential zones in the studied area is divided into five classes, which are very low, low, moderate, high, and very high.